2006
DOI: 10.1113/jphysiol.2005.102442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise‐induced arterial hypoxaemia and work rate on diaphragmatic fatigue in highly trained endurance athletes

Abstract: Diaphragmatic fatigue occurs in highly trained athletes during exhaustive exercise. Since approximately half of them also exhibit exercise-induced arterial hypoxaemia (EIAH) during high-intensity exercise, the present study sought to test the hypothesis that arterial hypoxaemia contributes to exercise-induced diaphragmatic fatigue in this population. Ten cyclists (V O 2 max : 70.0 ± 1.6 ml kg -1 min -1 ; mean ± S.E.M.) completed, in a balanced ordering sequence, one normoxic (end-exercise arterial O 2 saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
5
22
1
1
Order By: Relevance
“…Powers et al shown the difference % SaO 2 between resting and at the 100% VO 2max ranged from 4% in one subject to 16% in another [31]. On the other hand, it appear that the mean SaO 2 values in our study are lower than have been reported in some previous studies [14][15][16][17] yet are similar to those from others [6,8,30,31]. The degree of EIAH is affected the muscle mass engagement in the exercise and the exercise modality [16,32].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Powers et al shown the difference % SaO 2 between resting and at the 100% VO 2max ranged from 4% in one subject to 16% in another [31]. On the other hand, it appear that the mean SaO 2 values in our study are lower than have been reported in some previous studies [14][15][16][17] yet are similar to those from others [6,8,30,31]. The degree of EIAH is affected the muscle mass engagement in the exercise and the exercise modality [16,32].…”
Section: Resultssupporting
confidence: 75%
“…Previous studies have shown a greater drop in the SaO 2 at both maximal and sub-maximal exercise during treadmill running compared with ergometer cycling [16,33]. In the present study, we used incremental treadmill exercise while some studies used incremental exercise on cycle ergometers that have displayed higher [13][14][15][16][17]. Differences of exercise modality and protocol types used may help to explain the differences in SaO 2 measured.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The most likely reason why the diaphragm's fatigue threshold of force output is lower during exercise than at rest is that at rest the volitional increases in diaphragmatic force output are probably met by an adequate blood flow supply to the diaphragm, whereas during exercise there may be competition for blood flow between the diaphragm and locomotor muscles (210,212). This imbalance of diaphragmatic force output and O 2 transport to the diaphragm occurs most consistently when endurance exercise elicits at least 80% to 85%V o 2 max (246, 328) or less than 85% Sao 2 (44,545,546).…”
Section: Factors Contributing To Exercise-induced Respiratory Muscle mentioning
confidence: 93%
“…In healthy young adults of varying fitness, an imbalance of muscle force output versus blood flow or O 2 transport availability to the diaphragm that favors fatigue appears to occur most consistently when the intensity of prolonged endurance exercise elicits at least 80 -85% of V O 2max (52) or arterial O 2 saturation drops below ϳ85% (10,135,136).…”
Section: Exercise-induced Respiratory Muscle Fatiguementioning
confidence: 99%